2020
DOI: 10.1007/s00508-020-01793-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex and age differences in COVID-19 mortality in Europe

Abstract: Summary Aim To examine the magnitude of sex differences in survival from the coronavirus disease 2019 (COVID-19) in Europe across age groups and regions. We hypothesized that men have a higher mortality than women at any given age but that sex differences will decrease with age as only the healthiest men survive to older ages. Methods We used population data from the Institut National D’Études Démographiques on cumulative deaths due to COVID-19 from Februar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
2
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 33 publications
12
70
2
5
Order By: Relevance
“…The results of the study revealed that irrespective of age, the male gender was noted to be at increased risk of death due to COVID-19 than the female counterparts of the same age. 36 COVID-19 is reported to cause venous thromboembolic events that can result in adverse outcomes. The exaggerated coagulopathic state observed in patients can lead to the formation of fibrin clots.…”
Section: Variable Clinical Outcomes In Relation To Gendermentioning
confidence: 99%
“…The results of the study revealed that irrespective of age, the male gender was noted to be at increased risk of death due to COVID-19 than the female counterparts of the same age. 36 COVID-19 is reported to cause venous thromboembolic events that can result in adverse outcomes. The exaggerated coagulopathic state observed in patients can lead to the formation of fibrin clots.…”
Section: Variable Clinical Outcomes In Relation To Gendermentioning
confidence: 99%
“…[84][85][86][87][88][89] The most severe risk group for SARS-Cov-2 is the elderly. [90][91][92] While the overall case fatality rate (CFR) has been estimated to be around 4%, the rate is rapidly increasing in the age group of ≥60 years, reaching 16.9% and 24.4% in the 70-79 years and ≥80 years age groups, respectively. 91,92 More than 85% of the deceased are 65 years or older.…”
Section: There Is No Authorized Vaccine For Human Corona Viruses and Vaccines Against Common Cold Viruses Are Short-lived And Less Effectmentioning
confidence: 99%
“…However, such social regression is not based on the fallacies of female disabledbodiedness during disaster/conflict or biological vulnerability, but rather on the effects of living the pandemic under a patriarchal civilisation. Several studies (Ahrenfeldt et al, 2021;Bwire, 2020;Jin et al, 2020;Kopel et al, 2020;Sharma et al, 2020) have expounded that men actually have higher mortality rates than women regardless of their age, and also hypothesised on possible effects on men's fertility, as SARS-CoV-2 binds with the ACE2's coronavirus receptors in testicles (Illiano et al, 2020). The reasons are still being under review, though it has been suggested that it can be due to genetic reasons and health and social habits like high-risk behaviours, e. g. smoking and drinking.…”
Section: Is the Covid-19 Pandemic A Feminist Dystopia?mentioning
confidence: 99%